Political activists as free-riders: Evidence from a natural field experiment - Anselm Hager; Lukas Hensel; Johannes Hermle; Christopher Roth (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
How does a citizen's decision to participate in political activism depend on the participation of others? We conduct a nation-wide natural field experiment in collaboration with a major European party during a recent national election. In a party survey, we randomly provide canvassers with true information about the canvassing intentions of their peers. When learning that more peers participate in canvassing than previously believed, canvassers significantly reduce both their canvassing intentions and behavior. An additional survey among party supporters underscores the importance of free-riding motives and reveals that there is strong heterogeneity in motives underlying supporters' behavioral responses.
Keywords: D8; P16; 330; Political activism; natural field experiment; strategic behavior; beliefs; motives